The minority or the misunderstood? A young man's journey with anorexia nervosa. Issue 5 (1st August 2021) - Corcoran, Rachael; Trainor, Gemma; Robinson, Ben
Abstract: Introduction: Despite findings that 1 in 4 eating disorder sufferers are male (Beat, 2017), they continue to be known as "female" disorders, an association which delays diagnosis in males and prevents them from seeking the help that they need to recover. Aim: The current paper aimed to challenge this misconception by enabling and supporting Ben, a young male diagnosed with Anorexia Nervosa aged 16, to share his experience of seeking and receiving treatment for the disorder. Method: It achieved this by exploring how his disorder developed, his experience of a child and adolescent inpatient service and the events leading up to this, and his life post‐discharge, all in collaboration with Ben himself and using his own words. Discussion: The paper concludes with some implications for future practice, including that eating disorders should not be skewed towards any gender, treatment programmes need to ensure full inclusivity of males, and more gender sensitive information is required to raise awareness of this population and thus reduce the stigma and isolation they experience at present. It is hoped that these, along with the rest of the paper, will be accessible to and utilized by both professionals and non‐professionals alike. Accessible summary: ● Around one quarter of people diagnosed with an eating disorder are male, yet they continue to be known as "female" disorders. Because of this, young males are often missed by the system and as a result, receive treatment later than they should. They are currently underrepresented in services. ● This paper challenges the association above by supporting a young man who suffered with a type of eating disorder known as Anorexia Nervosa to share his journey from his personal perspective. It provides great insight into what it is like to be a male with an eating disorder, including how it felt to be the only male in an inpatient facility surrounded by females with the same disorder. ● The paper also provides important information for professionals working in the area. For example, eating disorders, including Anorexia Nervosa, should not be associated with one specific gender, and treatment programmes for young people with eating disorders should ensure they are appropriate for both females and males. As a society, we need to challenge the stigma which exists for males in admitting when they are struggling and asking for help, and we need to do everything we can to ensure that young men are picked up earlier in the system, in order to give them the best chance of recovery. ● It is hoped that Ben's story and the recommendations from it can go on to help other males who might be struggling.